Treatment of systemic arterial hypertension: an integrative literature review about Hydrochlorothiazide vs Chlortalidone - Nascimento, Yan Santiago (2022)
Objective: To carry out an integrative literature review seeking to analyze the main differences in the use of Hydrochlorothiazide vs Chlorthalidone, in order to understand whether any drug overlaps the other. Methodology: This integrative literature review was carried out, analyzing articles from January 2010 to June 2022, in Portuguese, English and Spanish in the following databases: MEDLINE via PubMed, Europe PMC, Lilacs and SciELO. The descriptors used were “Chlorthalidone”, “Hydrochlorothiazide” and “Hypertension”, according to the DeCS, covering 31 articles at the end. Results: Several studies point to a more intense effect of chlorthalidone on hydrochlorothiazide, but emphasize that the former has greater adverse effects, such as hypokalemia and hyponatremia. Some studies show that the use of chlorthalidone over hydrochlorothiazide brought about a reduction in cardiovascular risk of approximately 18%, a result that has been much debated in the literature as it is the result of an indirect meta-analysis. Conclusion: The literature still differs regarding the use of chlorthalidone over hydrochlorothiazide, requiring further conclusive studies on the direct comparative effect between the two drugs. Literature data converge that chlorthalidone has a more intense effect than hydrochlorothiazide, bringing, however, more adverse effects to the patient, such as hyperkalemia, for example.